Exploring Reading Strategy Use in Native and L2 Readers. Issue 7 (8th August 2020) - Feller, Daniel P.; Kopatich, Ryan D.; Lech, Iwona; Higgs, Karyn
ABSTRACT: Research comparing the reading strategy use of native and second language (L2) readers has often relied on self-report measures and has, at times, been conducted without measures of reading proficiency. In the present study we used regression and Bayes' factors to explore how L2 reader status and reading proficiency relate to self-report reading strategy use and the use of situated text processing strategies (i.e., paraphrasing, bridging, and elaboration). Data were collected from a South Central community college district as part of an ongoing study. L2 status did not predict self-reported strategy use, bridging, or elaboration but was associated with increased paraphrasing (in the regression analysis only). Reading proficiency was negatively associated with self-reported use of support strategies but positively predicted the use of all situated processing strategies. Results have important implications for L2 learning and instruction and provide insights into aspects of assessment for L2 readers.